LOVE AND UNDERSTANDING AS THE REFLECTION OF RELIGIOUS MODERATION IN THE NOVEL LOVE FROM A TO Z BY S.K. ALI (2019) - Nanda Hidayat; Dahlan; Sandra Dewi Dahlan (2025)
This study explores Love and Understanding as the reflection of religious moderation in the novel Love from A to Z by S.K. Ali and focuses on how the values of love and understanding influence the characters’ response to prejudice and diversity. This study uses a Qualitative method and applies the theory of Genetic Structuralism by Lucien Goldmann to examine how the author's socio-historical structure as a Muslim woman in the West shapes these values. The findings reveal that Love from A to Z depicts key aspects of religious moderation, including tolerance, anti-violence, acceptance of tradition, and national commitment through the acts of the characters. The study also finds that the author’s identity as a South Asian Canadian Muslim and her experiences in a post 9/11 Western strongly shaped the novel. Muslim authors like S.K. Ali have emerged to promote and convey to the world the true essence of Islam, especially in response to the widespread misunderstandings and misconceptions in the media about Muslims themselves. By examining how moderation is conveyed through narrative, this research highlights the role of literature in promoting understanding across religious and cultural differences.